Поведінка хвиль поляризації на межах поділу геологічних структур - Мороз, І.П. (Геоінформатика, 2015)
Розглянуто задачу про взаємодію хвиль поляризації (процес просторових коливань електричних диполів) з межею поділу двох матеріальних середовищ. Установлено умови, які повинні виконуватись на межі поділу середовищ, для функцій, що описують процес поширення хвиль. Такі функції визначають усереднені значення нормальних складових вектора “деформації” електронних оболонок атомів речовини та вектора коливальної швидкості електронних оболонок. В основу аналізу покладено підходи класичної електродинаміки та механіки суцільного середовища. Результати роботи можна використовувати для аналізу хвильових процесів у геологічних структурах. Рассмотрена задача о взаимодействии волн поляризации (процесc пространственных колебаний электрических диполей) с границей раздела двух сред. Определены условия для функций, описывающих процесс распространения волн на границе раздела сред. Такие функции определяют усредненные значения нормальных составляющих вектора “деформации” электронных оболочек атомов вещества и вектора колебательной скорости электронных оболочек. Анализ основан на подходах классической электродинамики и механики сплошных сред. Результаты работы могут использоваться при анализе волновых процессов в геологических структурах. Purpose. The purpose of the paper is to carry out theoretical investigation of the interaction of waves polarization (process of the electric dipoles spatial oscillations) with the boundary between two media. To give a definition of the boundary conditions for the functions describing the wave polarization propagation. Design/methodology/approach. The study is based on the approaches of classical electrodynamics and mechanics of continua. In the proofs, we used the condition of continuity of the normal component of the induction electric field vector, the continuity equation in the integral form, the continuity condition. Environment is a system of the electrons related to the atomic cores moving under the influence of external forces. Cores considered fixed. Findings. We defined the average values of the normal component of the vector “deformation” of the electron shells of substance atoms and an oscillatory velocity vector of the electron shells. It is shown that the indicated values change by discontinuous jump on the media boundary. We determined the coefficients of reflection and transmission of a plane polarization wave for normal incidence onto the interface. Reflection and transmission coefficients are dependent on the values of the relative permittivity, dielectric susceptibility, and the concentration of the bound electrons. Practical value/implications. The resulting boundary conditions are the basis for mathematical modeling of the polarization wave propagation in a multilayer medium. The results can be used for theoretical justification of a spectral analysis algorithm for data probing geological structures by the method of short-pulse field.